ANALISIS KEKASARAN PERMUKAAN BENDA KERJA PADA PEMBUBUTAN MATERIAL BAJA KARBON - Marten Bidangan (AgroSainT, 2010)
This research aimed to find out (1) the influence of cutting variable on the surface ronghness of the speciment; (2) the correlation between cutting variable on the surface ronghness of the of speciment; (3) the setting variable of cutting process which gave optimum the surface ronghness of the speciment. This research used the material of carbon steel and lathe chisel of high speed steel. This research used one instruments namely the instrument used to measure surface ronghness to find out the surface ronghness. The results show as follows: (1) Based on the statistic method the surface ronghness indicates that there is an influence of cutting variable on the surface ronghness. The cutting variable influence on the surface ronghness for speciment for the depth of 0,3 mm the influenced of mayor cutting edge is 10,30 % ; 1.90% for minor cutting edge; 1,10% for back growl edge; 49,10 for cutting speed and 34,70% feeding speed. Surface ronghness of the speciment is influenced by cutting speed, feeding speed, and major cutting edge.